Optimizing timing for emergency vehicle approaching warnings - Kajsa Weibull; Björn Lidestam; Erik Prytz (Acta Polytechnica CTU Proceedings, 2024)
Emergency driving is a demanding task. The ITS service Emergency Vehicle Approaching provides drivers with an in-car warning that an emergency vehicle is approaching. To ensure that the warning is efficient and reliable it must have a suitable timing. The EVA warning must be presented early enough to allow the driver to make a safe move-over maneuver. However, the distribution of EVA warnings is based on the most probable path of the emergency vehicle. If an EVA warning is distributed too early, it increases the risk of false alarms. In addition, if a warning is given too early the driver might deem it as irrelevant. Previous studies have distributed EVA warnings based on the distance between the emergency vehicle and surrounding cars. However, if the speed of the vehicle is not accounted for there is a risk of insufficient time for the driver to prepare for the emergency vehicle interaction. To explore suitable EVA timing, post-survey data from five driving simulator studies where drivers were exposed to EVA warnings were analyzed. The results suggest that 15–20 seconds could be an appropriate EVA timing. However, the required time for a move-over maneuver depends on the complexity of the current traffic situation.